The ameliorative effect of the Pyracantha fortuneana (Maxim.) H. L. Li extract on intestinal barrier dysfunction through modulating glycolipid digestion and gut microbiota in high fat diet-fed rats. Issue 10 (20th September 2019) - Xu, Hang; Zhao, Chunfang; Li, Yutian; Liu, Ruiyu; Ao, Mingzhang; Li, Fengcheng; Yao, Yuting; Tao, Zhu; Yu, Longjiang
Abstract : Pyracantha fortuneana fruit extract (PFE) exhibits beneficial effects on IBF in association with the modulation of glycolipid digestion and gut microbiota in HFD-fed obese rats. Abstract : Pyracantha fortuneana fruits are consumed as a dietary supplement in China and attenuate obesity and metabolic disorders. Obesity is known to be associated with intestinal barrier dysfunction driven by hyperglycemia and gut dysbiosis. However, whether the health benefits of P. fortuneana fruits are linked with the intestinal barrier function (IBF) remains unknown. This study aimed to evaluate the restorative effects of P. fortuneana fruit extract (PFE) on the IBF. Sprague Dawley rats were fed with a chow, a high-fat diet (HFD), or a PFE-supplemented diet for 8 weeks. Results showed that PFE intervention ameliorated HFD-induced intestinal barrier dysfunction by attenuating impaired structural integrity, reducing the elevated lactulose/mannitol ratio, and improving the mRNA and protein expression levels of tight junction proteins in HFD-fed rats. The ameliorations were associated with a beneficial effect on glycolipid homeostasis, as evidenced from the PFE decreasing intestinal absorptive capacity based on the d -xylose excretory rate, lowering the expression of GLUT2 and inhibiting digestive enzyme activities. The proanthocyanidins in the PFE showed greater in vitro inhibition on α-amylase, α-glucosidase, and lipase compared with triterpenoid saponins. Furthermore, the ameliorations on the IBF were also associated with effects on the microbial composition based on 16S rRNA gene sequence analysis. Several bacterial groups, which were linked with gut barrier integrity, were modulated after PFE administration, that is, Actinobacteria, Bacteroidaceae, Corynebacteriaceae, Lactobacillaceae, and S24-7 were elevated and the HFD-induced increase in Clostridia, Ruminococcaceae, Oscillospira, and Flexispira was restored. These data provide evidence for the ameliorative effect of the PFE on diet-induced intestinal barrier functional alternations in association with its capacity to modulate glycolipid digestion and gut microbiota in HFD-fed obese rats.